The effect of cigarette smoking history on autonomic and cerebral oxygenation responses to an acute exercise bout in smokers. Issue 19 (11th October 2020) - Hartmann, Tegan E.; Marino, Frank E.; Duffield, Rob
Abstract: The extent of smoking history is causally linked to adverse cerebro‐ and cardiovascular health outcomes, while conversely, exercise decreases this risk and associated mortality. However, the acute cerebro‐ and cardiovascular responses to exercise in smokers are unknown, and may provide insight to understand chronic adaptation. This study examined the acute heart rate (HR) variability (R‐R intervals) and cerebral oxygenation responses to exercise in smokers compared to nonsmokers. Fifty‐four males classified as smokers ( n  = 27) or nonsmokers ( n  = 27) were allocated into either younger (YSM, YNS) or middle‐aged groups (MSM, MNS). Participants completed 40 min of stationary cycle ergometry at 50% of VO2peak. Cerebral oxygenation (near‐infrared spectroscopy) and autonomic function (HR variability) were collected before, during, and after exercise at 0, 30 min, 1, and 4 hr postexercise. The nonsmoker cohort (MNS and YNS) demonstrated higher values for the standard deviation ( SD ) of the R‐R interval (SDNN) and the root mean squared of the SD at 1 and 4 hr postexercise versus smokers ( p  < .05). The low frequency (LF) band in YSM was lower than in YNS at 1 hr ( p  < .05). However, LF and high frequency were higher for MNS compared to MSM at 1 hr ( p  < .05). Oxygenated hemoglobin during and following exercise were elevated in NS with values for MSM lower than YSM ( p  < .05). The findings show smoking history can affect cerebral oxygenation during and following an acute exercise bout. Further, following exercise, smokers may exhibit a delay or inhibition in parasympathetic activity. Abstract : The findings suggest an effect of smoking history on cerebral oxygenation during and following an acute exercise bout of exercise with nonsmokers demonstrating higher oxygenated haemoglobin compared to that of both young and middle‐aged smokers.